Effects of low and high doses of fenofibrate on protein, amino acid, and energy metabolism in rat - Holeček, Milan; Vodeničarovová, Melita (International journal of experimental pathology, 2020)
A feared adverse effect of dyslipidaemia therapy by fibrates is myopathy. We examined the effect of fenofibrate (FF) on protein and amino acid metabolism. Rats received a low (50 mg/kg, LFFD) or high (300 mg/kg, HFFD) dose of FF or vehicle daily by oral gavage. Blood plasma, liver, and soleus and extensor digitorum longus muscles were analysed after 10 days. The FF-treated rats developed hepatomegaly associated with increased hepatic carnitine and ATP and AMP concentrations, decreased protein breakdown, and decreased concentrations of DNA and triglycerides. HFFD increased plasma ALT and AST activities. The weight and protein content of muscles in the HFFD group were lower compared with controls. In muscles of the LFFD group there were increased ATP and decreased AMP concentrations; in the HFFD group AMP was increased. In both FF-treated groups there were increased glycine, phenylalanine, and citrulline and decreased arginine and branched-chain keto acids (BCKA) in blood plasma. After HFFD there were decreased levels of branched-chain amino acids (BCAA; valine, leucine and isoleucine), methionine, and lysine and increased homocysteine. Decreased arginine and increased glycine concentrations were found in both muscles in FF-treated animals; in HFFD-treated animals lysine, methionine, and BCAA were decreased. We conclude that FF exerts protein-anabolic effects on the liver and catabolic effects on muscles. HFFD causes signs of hepatotoxicity, impairs energy and protein balance in muscles, and decreases BCAA, methionine, and lysine. It is suggested that increased glycine and decreased lysine and methionine levels are due to activated carnitine synthesis; decreased BCAA and BCKA levels are due to increased BCAA oxidation.
Keywords: játra; lysin; Amino Acids, Branched-Chain; Humans; hypolipidemika; proteiny; Carnitine; carnitine; Lysine; Proteins; oxidace-redukce; methionine; krysa rodu Rattus; Glycine; Fenofibrate; glycin; lidé; Leucine; zvířata; hepatomegalie; potkani Wistar; aminokyseliny; Hepatomegaly; Amino Acids; hepatomegaly; kosterní svaly; Energy Metabolism; fibrates; Liver; energetický metabolismus; Rats, Wistar; Male; karnitin; Muscle, Skeletal; branched-chain amino acids; Hypolipidemic Agents; Oxidation-Reduction; Rats; větvené aminokyseliny; methionin; Methionine; Animals; fenofibrát; mužské pohlaví; leucin